Jantung, Medan magnet, Kesehatan KORELASI MASSA TUBUH TERHADAP DETAK JANTUNG PADA MENCIT BALB-C YANG DIPAPAR MEDAN MAGNET EXTREMELY LOW FREQUENCY (ELF) INTENSITAS 100 µT - Siti Hindun Hindiyati (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2023)
Exposure to an Extremely Low Frequency (ELF) magnetic field with an intensity of 100 µT has been set as a threshold value for health effects, but it still needs to be studied for its biological impact, especially on the function of the heart organ. This study aims to examine